Keadilan Prosedural Partisipatif dan Dukungan Organisasi Terhadap Kepuasan Kerja Karyawan: Studi Pada PT. Telkom Indonesia, Tbk Witel Cirebon - Asep Qustolani (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2020)
Job satisfaction is interesting and is considered important because of perceived job satisfaction can affect the overall organization of his net. To get optimal results, job satisfaction is one important factor, when a person feels satisfaction in working of course he will do everything possible with his ability to complete his work. Thus the results of its work will improve optimally.The results showed that participative procedural justice and organizational support had a significant effect on employee job satisfaction, which means better procedural participative justice and the better the organizational support to employees will increase job satisfaction.